2012
DOI: 10.1016/j.susc.2011.10.023
|View full text |Cite
|
Sign up to set email alerts
|

Studies of Li intercalation of hydrogenated graphene on SiC(0001)

Abstract: The effects of Li deposition on hydrogenated bilayer graphene on SiC(0001) samples, i.e. on quasi-freestanding bilayer graphene samples is studied using low energy electron microscopy, micro-low-energy electron diffraction and photoelectron spectroscopy. After deposition, some Li atoms form islands on the surface creating defects that are observed to disappear after annealing. Some other Li atoms are found to penetrate through the bilayer graphene sample and into the interface where H already resides. This is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 26 publications
2
27
2
Order By: Relevance
“…The energy separation between the G and SiC 0 components has now increased to the largest value observed, 3.0 eV. In earlier investigations on Si-face graphene, [4][5][6][7]9 this increase in energy separation has been attributed to intercalation of the metal at the graphene/SiC interface, thus to a change in the interface dipole layer that increases the separation between the components. Heating at progressively higher temperatures is seen to result in a gradual decrease in the separation, which indicates a gradual reduction of Li at the interface, since the initial C 1s spectrum is essentially restored after heating at 1030 C. The corresponding set of Si 2p spectra in Fig.…”
Section: Resultsmentioning
confidence: 81%
See 2 more Smart Citations
“…The energy separation between the G and SiC 0 components has now increased to the largest value observed, 3.0 eV. In earlier investigations on Si-face graphene, [4][5][6][7]9 this increase in energy separation has been attributed to intercalation of the metal at the graphene/SiC interface, thus to a change in the interface dipole layer that increases the separation between the components. Heating at progressively higher temperatures is seen to result in a gradual decrease in the separation, which indicates a gradual reduction of Li at the interface, since the initial C 1s spectrum is essentially restored after heating at 1030 C. The corresponding set of Si 2p spectra in Fig.…”
Section: Resultsmentioning
confidence: 81%
“…In this study, the effects induced in the electronic structure of C-face graphene are investigated after depositing similar amounts of Li and after heating at similar temperatures as earlier done [4][5][6] for Si-face graphene samples. The idea was to reveal if similar effects would be induced in the band structure and core levels.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Small Li atoms are expected to penetrate into the interlayer space (presumably, through Svacancies in the surface layer, similarly to H atoms [26]) more readily than larger Na and K. Note that Li can be intercalated into bilayer graphene, without any pronounced distortion of the structure [27]. The DFT calculations of Young's modulus for Li-intercalated bilayer and trilayer graphene have shown that the intercalation increases the intrinsic stiffness.…”
Section: Introductionmentioning
confidence: 99%
“…The bonds between the buffer layer and SiC can be broken by intercalation of foreign atoms, which therefore converts the buffer layer to a monolayer graphene and opens a way to tailor its electronic properties, i.e., by doping. Intercalation of many species such as H, O, F, Au, Li, Na, Ge, Si and Yb [13][14][15][16][17][18][19][20][21][22] varied graphene doping in a wide range from n-doped to p-doped materials. Si and Ge, both from group IV, can be intercalated and effectively decouple the buffer layer from its supporting SiC substrate [19,20,23,24].…”
Section: Introductionmentioning
confidence: 99%